(untitled) (Світ фінансів, 2017)
Письменний В. В. Самооподаткування: історичний досвід та сучасні проблеми. В історичній ретроспективі простежено етапи становлення та розвитку самооподаткування в Україні. Проаналізовано вітчизняний досвід справляння платежів із самооподаткування. Обґрунтовано алгоритм цієї форми мобілізації фінансових ресурсів. Установлено необхідність поширення в Україні практики самооподаткування мешканців територіальних громад. Pysmennyy V. Self-taxation in system of local fi nance of Ukraine. The stages of becoming and development of self-taxation in Ukraine are researched in a history retrospective. Native experience of operating practice of self-taxation is analysed. The algorithm of this form of mobilization of fi nancial resources is offers. The necessity of distribution of the self-taxation practice of territorial societies in our state is introduced.